Kesejahteraan Masyarakat Diukur Melalui Pengagguran, Inflasi dan Pertumbuhan Ekonomi di Kalimantan Tengah, Kalimantan Utara dan Kalimantan Timur - Pradanimas, Aqilla; Lifia; Yuliana, Indah; Rahayu, Yayuk Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Welfare of the people is a goal of every region, including Central Kalimantan, North Kalimantan and East Kalimantan. Welfare of the people measured using Human Development Index (HDI). There are many factors that influence welfare of the people. This purpose of study to analyze the effect of unemployment and inflation on welfare of the people with economic growth as an intervening. The research method used quantitative wita data from the Central Bureau of Statistics and Path analysis as an analytical technique. The results of study unemployment has a positive significant effect on welfare of the people, while inflation has a negative significant effect and economic growth has no significant effect. Unemployment has a negative significant effect on ecomic growth, while inflation has a positive significant. And economic growth cannot be an intervening variable. So to improve the welfare of the people it is necessary to play the role of governments in each province to really focus on allocating funds for health, education, employment expansion programs, skills improvement and effective and efficient poverty alleviation programs.